Realization of screen-printed silver paste grid contacts in the III-V solar cell - Qiangjian Sun; Junhua Long; Pan Dai; Xinzhou Wu; Erpeng Li; Min Zhou; Xiaoxu Wu; Zhitao Chen; Menglu Yu; Shuhong Nie; Qing Gong; Wencong Yan; et al. (Materials & Design)
The integration of screen-printed silver paste with III-V solar cells offers a promising approach to broaden potential application. Nonetheless, the challenge of establishing an ohmic contact between the narrow linewidth paste electrodes and the III-V contact layer remains unresolved. In this study, the screen-printing technology was developed to replace conventional alloy electrodes in III-V solar cells. The contact resistance between silver pastes and the InGaAs contact layer was systematically optimized, yielding a specific contact resistance of 5.79 × 10-5 Ω·cm2 at a low-temperature annealing of 300 °C. The performance enhancement is attributed to the capacity of silver particles in the paste to form interparticle contacts, thereby constructing efficient conductive pathways and reducing intrinsic resistance. Furthermore, the silver diffusion into the contact layer enhances the likelihood of the tunneling effect. To mitigate shadowing losses associated with screen-printed electrodes, the knotless grid design enabled the narrow grid line width of 26 μm in the InGaAs solar cell. The photovoltaic conversion efficiency of the screen-printed InGaAs solar cell reached 10.30 % under the AM1.5G spectrum, comparable to that of cells prepared by conventional e-beam and photolithography techniques.